New improvements to range image segmentation by edge detection. - Bellon, O.R.P.
This article presents new improvements to range image segmentation based on edge detection techniques. The developed approach better preserves the object's topology and shape even to noisy images. The algorithm also does not depend on rigid threshold values, thus being useful in unsupervised systems. Experiments were performed in a popular range image database and the results were compared to four other traditional range image segmentation algorithms, demonstrating the efficiency of the proposed algorithm
Keywords: Algorithm efficiency; Edge detection; Feature extraction; Noisy images; Object shape preservation; Object topology preservation; Range image database; Range image segmentation algorithms; Unsupervised systems